The bride's necklace eaudiobook - Martin, Kat (The Necklace Trilogy, 2016)
Knowing that she alone can protect her sister from the Baron Harwood, their lecherous stepfather, Victoria Temple Whiting snatches the family's heirloom necklace—believed to hold the power to bring great happiness or terrible tragedy—to pay for their escape to London. Terrified that the baron will find them, Victoria poses as Tory Temple and finds employment as a servant in the household of handsome Cordell Easton, the scandalous Earl of Brant. The sisters' arrival couldn't have been more welcome. In need of a new mistress, Cord turns to Tory, whose wit and intellect intrigue him. But when the baron discovers the girls' whereabouts, Cord learns Tory's secret—her noble birth. Furious that he has compromised the daughter of a peer, Cord must decide if he will marry Tory to keep her safe or allow his stubborn pride to deny his heart. Contains mature themes.